Attitudes and Experience of Malaysian Parents towards School Closure during the COVID-19 Pandemic - Chuong Hock, Ting; Jeffery, Stephen; Ahmad Khairi, Hassan; Norashikin, Abdul Moris; Noor Nasuha, Noor Hamal; Nurul Ain, Amidar; Mohd Azlan, Rusdi (USIM PRESS, 2021)
In 2020, the Coronavirus disease 2019 (COVID-19) pandemic had triggered the lockdown in many countries around the world. School closure was no exception as a measure to limit the spread of the disease. This step was expected to bring some impact on parents, especially if both of them were working. In this study, we aimed to investigate Malaysian parental attitudes and experiences during the COVID-19 pandemic. We conducted an online cross-sectional survey by using a structured questionnaire, between May and June 2020. A total of 273 parents with children aged below 18 years old were involved. Descriptive analysis was done to determine the sociodemographic data of the respondents, their attitudes, and their experiences associated with the school closure during the outbreak. 97.4 % of parents agreed with the school closure. The majority of them believed the outbreak was serious and the school dismissal was appropriate to protect their children and the community. However, only 54.9 % were well prepared for the measure. 11.4 % of parents had difficulty arranging childcare. During the outbreak, 85.7 % experienced missing work and 71.4 % felt at risk of losing their jobs. The school closure also indirectly incurred additional costs for 88.6% of the parents and partially contributed to 75.5% of the parents losing income. Unexpected long-term school closure might cause some adverse outcomes to the employed parents during a pandemic, therefore, the health authority and education department should take this into consideration when mitigating this issue.